Association of ABO Incompatibility With Red Blood Cell Indices of Cord Blood Unit - Shu-Huey Chen; Marie Lin; Kuo-Liang Yang; Teng-Yi Lin; His-Hsiu Tsai; Shang-Hsien Yang; Yu-Hsun Chang; Yi-Feng Wu; Tso-Fu Wang (Pediatrics and Neonatology, 2012)
Maternal–fetal ABO incompatibility is one of the causes of neonatal hyperbilirubinemia. We postulate that hemoglobin (Hb), hematocrit (Hct), and red blood cell (RBC) values for cord blood units (CBUs) are lower and erythroblast values higher for maternal–fetal ABO incompatible dyads than for compatible dyads. Objective: We investigated the relationship between Hb, Hct, RBC, and erythroblast CBU values and maternal–fetal ABO blood type compatibility. Methods: Mothers having blood group O who gave birth to infants with blood group A, B, or AB were classified as Group I. According to baby’s blood group, the members of Group I were further divided into AO (baby group A, mother group O), BO (baby group B, mother group O), and ABO (baby group AB, mother group O) subgroups. Mothers having blood group A who gave birth to infants with blood group B or AB and mothers having blood group B who gave birth to infants with blood group A or AB were classified as Group II. All other maternal–fetal blood type pairs were considered ABO compatible and were classified as Group III. We compared mean Hb, Hct, RBC, and erythroblast values for the infants’ CBUs among these three groups including the subgroups of Group I. Results: Group I had lower mean Hb, Hct, and RBC values than Group II and Group III (both p < 0.001). Although the mean Hb, Hct, and RBC values for Group II were lower than for Group III, the difference was not statistically significant. Mean Hb and RBC for the AO group were higher and nucleated RBC (nRBC) ratios were lower than for the BO group; however, these differences were also not statistically significant. Interestingly, the mean Hct value of the BO group was significantly lower than that of the AO group (p = 0.04). Conclusion: Group A or B neonates with a group O mother have lower mean Hb, Hct, and RBC values for CBUs than other neonates. The role of RBC indices in predicting neonatal hemolytic hyperbilirubinemia remains unclear and further studies are needed to identify the possible clinical association.